Le « montage » dans l’esthétique poétique de Roxana Miranda Rupailaf (poète Mapuche Huilliche) - Claudia Arellano Hermosilla (Appareil)
The text that follows, examines how the esthetic-poetics of Roxana Miranda Rupailaf materializes a discursive place from and to the abject, capable of threatening the homogeneity of the founding myths of Judeo-Christian tradition. If the abject problematized identities once the limits are crossed, what is at stake would be the construction of new subjectivities, always in a continuous process of production and reproduction of symbolic capital. It is through the power of literature that we can rebuild the assemblies of historically made speeches and load them again with meanings.